Mother Goose as a Resource in Teaching Historical Linguistics - Dallin D. Oaks (Journal of Linguistics and Language Teaching)
Mother Goose and other nursery rhymes as authentic texts are valuable resources that can be used effectively to illustrate historical English language change. Even though these nursery rhymes contain some forms, structures, and word meanings that differ from the language of today, the texts are sufficiently recent that they are intelligible to modern audiences. This article will illustrate the relevance and usefulness of nursery rhymes in teaching about principles of language and language change, such as voicing, phonological processes, factors motivating phonological change, as well as actual changes in the phonology, morphology, syntax, semantics, and lexicon of English.